Parental genetic effects on the offspring’s phenotype without transmission of the gene itself: pathophysiology and clinical evidence - Zhang, Xiaoli; Hocher, Berthold (American journal of physiology. Cell physiology, 2024)
Parental genes can influence the phenotype of their offspring through genomic-epigenomic interactions even without the direct inheritance of specific parental genotypes. Maternal genetic variations can affect the ovarian and intrauterine environments and potentially alter lactation behaviors, impacting offspring nutrition and health outcomes independently of the fetal genome. Similarly, paternal genetic changes can affect the endocrine system and vascular functions in the testes, influencing sperm quality and seminal fluid composition. These changes can initiate early epigenetic modifications in sperm, including alterations in microRNAs, tRNA-derived small RNAs (tsRNAs), and DNA methylation patterns. These epigenetic modifications might induce further changes in target organs of the offspring, leading to modified gene expression and phenotypic outcomes without transmitting the original parental genetic alterations. This review presents clinical evidence supporting this hypothesis and discusses the potential underlying molecular mechanisms. Parental gene-offspring epigenome-offspring phenotype interactions have been observed in neurocognitive disorders and cardio-renal diseases.